Anne of green gables - Montgomery, L.M (Tom Doherty, 1995)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her